The Relationship Among Gastrointestinal Symptoms, Problem Behaviors, and Internalizing Symptoms in Children and Adolescents With Autism Spectrum Disorder - Ferguson, Bradley J.; Dovgan, Kristen; Takahashi, Nicole; Beversdorf, David Q. (Frontiers in Psychiatry, 2019)
Background: Many individuals with autism spectrum disorder (ASD) have co-occurring gastrointestinal (GI) symptoms, but the etiology is poorly understood. These GI symptoms often coincide with problem behaviors and internalizing symptoms, which reduces the quality of life for these individuals. Methods: This study examined the relationships among GI problems, problem behaviors, and internalizing symptoms in a sample of 340 children and adolescents with ASD who are patients at the University of Missouri Thompson Center for Autism & Neurodevelopmental Disorders. Results: The majority of patients experienced constipation (65%), about half experienced stomachaches or stomach pain (47.9%), and others experienced nausea (23.2%) or diarrhea (29.7%). Young children with aggressive problem behaviors were 11.2% more likely to have co-occurring nausea; whereas, older children showed more complex relationships between internalizing symptoms and GI symptoms. Older children with greater anxiety symptoms were 11% more likely to experience constipation, but 9% less likely to experience stomachaches. Older children with greater withdrawn behavior were 10.9% more likely to experience stomachaches, but 8.7% less likely to experience constipation. Older children with greater somatic complaints were 11.4% more likely to experience nausea and 11.5% more likely to experience stomachaches. Conclusions: Results suggest that the presentation of externalizing problem behavior and internalizing symptoms associated with GI problems differs between young children and adolescents with ASD. Therefore, behavior may have different relationships with GI symptoms at different ages, which may have implications for the treatment of and clinical approach to GI disturbances in ASD.